2014
DOI: 10.2136/vzj2014.03.0032
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Controls on Gas Flow Directions in a Waste Rock Dump

Abstract: A fatal accident at a mine waste rock dump was thought to be due to the downward low of O 2deicient air originating from the dump. A numerical model tested the plausibility of various physical mechanisms hypothesized to control gas low in the dump. The main initial hypotheses were that gas low leading to the incident was due to the sole or combined effect of changes in barometric pressure, temperature, or till cover water saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…S4). The observed significance of O 2 advection supports previous work showing that even small pressure gradients (<1 Pa m −1 ) can cause significant viscous fluxes in porous media (Elberling et al, 1998) and that advection can be a dominant O 2 supply mechanism in coarse waste rock (Amos et al, 2009; Pantelis et al, 2002; Lahmira et al, 2014; Pantelis and Ritchie, 1991). At the same time, the advective O 2 transport appears to more strongly depend on waste‐rock porosity and pore‐water saturation than diffusion (e.g., diffusion and advection vary 5 and 10 orders of magnitude, respectively, as a function of saturation), which is a reflection of the fact that the effective air permeability, like D eff , varies greatly with particle size and pore‐water saturation (Supplemental Table S2).…”
Section: Resultssupporting
confidence: 87%
“…S4). The observed significance of O 2 advection supports previous work showing that even small pressure gradients (<1 Pa m −1 ) can cause significant viscous fluxes in porous media (Elberling et al, 1998) and that advection can be a dominant O 2 supply mechanism in coarse waste rock (Amos et al, 2009; Pantelis et al, 2002; Lahmira et al, 2014; Pantelis and Ritchie, 1991). At the same time, the advective O 2 transport appears to more strongly depend on waste‐rock porosity and pore‐water saturation than diffusion (e.g., diffusion and advection vary 5 and 10 orders of magnitude, respectively, as a function of saturation), which is a reflection of the fact that the effective air permeability, like D eff , varies greatly with particle size and pore‐water saturation (Supplemental Table S2).…”
Section: Resultssupporting
confidence: 87%
“…These studies have demonstrated that the processes are coupled and their analysis cannot be done separately. Subsequently, research in this area has focused on developing environmental protection methods (Wilson et al, 2000b;Fala et al, 2005Fala et al, , 2006Aubertin et al, 2005;Aubertin, 2013;Martin et al, 2005;Molson et al, 2005Molson et al, , 2008Dawson et al, 2009;Raykaart and Hockley, 2009;Lefebvre et al 2011;Lahmira et al 2014aLahmira et al , 2014bBroda et al, 2015). For new sites, the choice of a waste rock pile construction method is related to practical considerations and economic constraints, in addition to environmental issues (Wels et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lefebvre et al (2001b) demonstrated the occurrence of convection for low‐permeability material with limited temperature increases, even for a limited pile height. In addition, Lahmira et al (2014) showed that convection can occur even in cold and covered piles. However, the fine‐grained nature and relatively high moisture content of the uppermost waste‐rock layer, which includes the traffic surface, inhibits the development of convection cells and therefore limits the contribution of convective gas transport (Lefebvre et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…Pore‐gas composition in full‐scale waste‐rock dumps has been monitored in the past (Harries and Ritchie, 1985; Lundgren, 2001; Lefebvre et al, 2001a; Lahmira et al, 2014). Multilevel monitoring wells installed in operational or reclaimed dumps have provided depth‐discrete information on pore‐gas composition and related parameters (Linklater et al, 2005; Sracek et al, 2006).…”
mentioning
confidence: 99%